Substrate‐Controlled Divergent Synthesis of Enaminones and Pyrroles from Indolizines and Nitroso Compounds. Issue 21 (12th September 2019) - González‐Soria, María José; Alonso, Francisco
Abstract: It is imperative to learn new synthetic transformations to succeed in drug discovery and development. We report the substrate‐driven synthesis of β‐enaminones and N ‐aryl pyrroles from indolizines and nitrosoarenes; aryl‐substituted indolizines lead to β‐enaminones in a regio‐ and diastereoselective manner, whereas alkyl‐substituted indolizines produce tetrasubstituted pyrroles. All products contain a pyridine unit, the second most abundant ring (after phenyl) in the FDA Orange Book. In both cases, the reactions proceed at room temperature without any catalyst. Moreover, both types of products can be obtained in one pot from commercial materials as well as at a gram scale. It is worthy of note that the regioselectivity of the β‐enaminones is inaccessible by the standard literature methods and their utility has been exemplified in the synthesis of diverse heterocycles. We have made every endeavor to put forward the corresponding reaction mechanisms based on thorough experimental work. Abstract :